PENGEMBANGAN LKPD (LEMBAR KERJA PESERTA DIDIK) MATEMATIKA BERBASIS DISCOVERY LEARNING BERBANTU QR CODE PADA MATERI PELUANG KELAS XII SMA MUHAMMADIYAH 1 PEKALONGAN - Rizky Ramadhan; Nurul Farida; Dwi Rahmawati (Universitas Muhammadiyah Metro, 2024)
The aim of the research is to produce a product in the form of valid and practical worksheets for discovery learning students based on QR Code. The type of development research used in this research is the 4D model which has 4 stages, Define, Design, Develop, and Disseminate, but this research is only carried out until the Develop stage. This research was conducted at SMA Muhammadiyah 1 Pekalongan. The research subjects were class XII students of SMAN 1 Pekalongan. The data collection instruments used were media expert validation questionnaires, material expert questionnaires and student response questionnaires. The validity test was carried out on 4 expert validators, namely 2 media expert validators, and 2 material expert validators. The practicality test was carried out on 6 class XII students of SMA Muhammadiyah 1 Pekalongan. The product developed has been validated by media experts and material experts, the results obtained from the validation of design experts are 99% with very valid criteria, 90% material experts with very valid criteria, and small group trials obtained 92% results with very practical criteria. Based on the results of expert validation and small group trials, the developed LKPD product is very valid and very practical to use.